Analysis of the distribution shift of detected aneuploidies by age independent first trimester screening - Schmidt, Peter; Hörmansdörfer, Cindy; Golatta, Michael; Scharf, Alexander (Archives of gynecology and obstetrics, 2010)
First trimester screening (FTS) became standard in non-invasive testing for chromosomal abnormalities in early pregnancy. The individual risk is calculated on the basis of a general background risk, which refers to the maternal age. A new method, Advanced Firsttrimester Screening (AFS) excludes the background risk in its algorithm. This study had the aim to analyze how the detection of aneuploidies is influenced by the in- or exclusion of the maternal age in the risk calculation.